Diversity, equity, and inclusion in the Blue Economy: Why they matter and how do we achieve them? - Issifu, Ibrahim; Dahmouni, Ilyass; Deffor, Eric Worlanyo; Sumaila, U. Rashid (Frontiers in Political Science, 2023)
The Blue Economy (BE) has captured the attention of diverse interests to the ocean and there is rising concern about making it more equitable and inclusive. As it currently stands, diversity, social equity, and inclusion considerations have not been foregrounded in the discourse surrounding the BE and are continuously overlooked and undervalued. This paper reviews the ongoing social inequalities in the BE and distribution of benefits and costs across different groups in society. It also explores why equity matters, and how it can be achieved. Mirroring the call for under-represented or marginalized social groups to receive a fair share of the returns, which may be more than they have received to date. Our analysis shows that between 1988 and 2017, a Germany–based company has registered about 39% of all known marine genetic resources, while three companies in Asia control 30% of the market share of seafood sector in 2018. These findings show high consolidation of the ocean space by top corporations. Therefore, this paper argues that the exclusion of equity considerations within the BE investments can undermine ocean-based activities such as marine wildlife conservation initiatives that may disrupt the ocean sustainability agenda.